1977
DOI: 10.1148/124.2.419
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Imaging with123l-Hexadecenoic Acid

Abstract: 123I-hexadecenoic acid is a terminally iodinated, 17-carbon fatty acid analog which is rapidly degraded in the myocardium. By determining regional myocardial distribution patterns and clearance rates, it may become useful as a single agent for estimating regional myocardial perfusion and for distinguished viable ischemic tissue from infarcted tissue. The high count rates obtainable with the iodine label permit acquisition of qualitative multiprojection images in only 3 min. per view, or quantifiable single pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…In mid 1970's, several iodinated long chain fatty acids were developed by introducing radioiodine to the terminal position of fatty acids without altering extraction efficiency compared with the natural compound [19][20][21]. These straight chain fatty acids, 123 Ihexadecanoic acid (IHXA) and 123 I -heptadecanoic acid (IHDA) were proved to be an indicator of myocardial perfusion in canine model and human [20,21]. After rapid initial myocardial extraction these traces showed biexponential clearance similar to that of 11 Cpalmitate with rapid and slow components, those were thought to represent β-oxidation of fatty acids and fatty acids storage in lipid pool, respectively.…”
Section: Tracers For Fatty Acid Imaging For Spect (Fig 3)mentioning
confidence: 99%
See 1 more Smart Citation
“…In mid 1970's, several iodinated long chain fatty acids were developed by introducing radioiodine to the terminal position of fatty acids without altering extraction efficiency compared with the natural compound [19][20][21]. These straight chain fatty acids, 123 Ihexadecanoic acid (IHXA) and 123 I -heptadecanoic acid (IHDA) were proved to be an indicator of myocardial perfusion in canine model and human [20,21]. After rapid initial myocardial extraction these traces showed biexponential clearance similar to that of 11 Cpalmitate with rapid and slow components, those were thought to represent β-oxidation of fatty acids and fatty acids storage in lipid pool, respectively.…”
Section: Tracers For Fatty Acid Imaging For Spect (Fig 3)mentioning
confidence: 99%
“…After rapid initial myocardial extraction these traces showed biexponential clearance similar to that of 11 Cpalmitate with rapid and slow components, those were thought to represent β-oxidation of fatty acids and fatty acids storage in lipid pool, respectively. However, a canine study suggested that washout rate of radioactivity from the heart reflected the back diffusion of deiodinated free iodine not by β-oxidation [20]. A clinical study with IHDA demonstrated high image quality early after injection but it deteriorated rapidly because of rapid reduction of myocardial counts and increase in background counts by deiodinated radioiodine [23].…”
Section: Tracers For Fatty Acid Imaging For Spect (Fig 3)mentioning
confidence: 99%
“…1) In mid 1970's, several iodinated long chain fatty acids were developed by introducing radioiodine to the terminal position of fatty acids without altering extraction efficiency compared with the natural compound [14][15][16]. These straight chain fatty acids, 123 I-hexadecanoic acid (IHXA) and 123 I -heptadecanoic acid (IHDA) were proved to be an indicator of myocardial perfusion in canine model and human [15,16]. After rapid initial myocardial extraction these traces showed biexponential clearance (rapid and slow components) similar to that of 11 C-palmitate.…”
Section: Myocardial Fatty Acid Uptake and Metabolismmentioning
confidence: 99%
“…With a myocardial half-life of 25 min (196), 1231-labeled hexadecenoic acid demonstrated ischemic defects in patients with coronary artery disease (196) or infarctions (197). The extraction rate of -70% was comparable to that of potassium 43 (198).…”
Section: Cold Spot Imagingmentioning
confidence: 99%